Komunikasi Interpersonal Guru dan Minat Belajar Siswa - Aziz, Jamil Abdul (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
The purpose of education will not be realized without the presence of educators who are skilled in carrying out the ongoing education process. One of the important teacher skills is communication skills. That is what makes the reason for researchers to take the issue of interpersonal communication of teachers and students with student interest in learning at MTs Muhammadiyah 1 Ciputat. In this study, researchers used a correlational analysis method, with a quantitative approach. Data collection tools include: interviews, observation, documentation and questionnaires. This questionnaire distribution technique uses random sampling techniques. As for processing the data after the data from the questionnaire was obtained, researchers used the formula 'r' product moment. The results showed there was a positive influence or correlation between teacher and student interpersonal communication (Variable X) with student learning interest (Variable Y) in the subjects of Islamic Cultural History.